Ministry Of Rural Development, Sarawak (MRD) / Halimatussaadiah Abdul Hai - Abdul Hai, Halimatussaadiah (University Technology MARA Sarawak, 2013)
Ministry of Rural Development Sarawak was established in January 2, 1998 also known as Ministry of Land Development.On July 1, 2004 ministry been reshuffled and divided into two namely Ministry of Rural Development and Ministry of Land Development and also represented by Minister and Permanent Secretary. Ministry of Rural Development (MRD), Sarawakians responsible for ensuring the planning, implementation and monitoring of government policies related to programs of rural development can be implemented efficiently and effectively through the use of available resources in order to improve the socio-economic status of the particular rural population. Ministry of Rural Development located at Bangunan Baitulmakmur, Petra Jaya. All ministries in the Bangunan Baitulmakmur are under Baitulmal and all the audit will be in charge by Baitulmal. Everything about the administration and management will be in charge by Baitulmal.